Gestión administrativa en la ebanistería hasta la sonrisa es seria de la parroquia La Unión del cantón Babahoyo provincia Los Ríos periodo 2023. - Uchubanda Ochoa, Arelys Jazmín (2025)
Administrative management and job performance are fundamental pillars in the success of private institutions In this study, the impact of administrative management on the job performance of the operational, administrative and support staff of the Ebanistería Hasta La Sonrrisa of the La Unión parish is evaluated for the period 2023. A mixed methodological approach was used, covering both quantitative and qualitative techniques. Data were collected through surveys, interviews and document review. Data analysis included descriptive statistics and thematic analysis. The findings reveal a positive relationship between effective administrative management and optimal staff job performance. Key parameters were identified to measure job performance in administrative management, including planning, organization, direction and control. Factors that influence job performance, such as leadership, communication, teamwork and motivation, were analyzed. Efficient administrative management positively impacts the work performance of the employees of the Ebanistería Hasta La Sonrrisa in the parish of La Unión for the period 2023. It is recommended to implement strategic actions to strengthen administrative management, focusing on the identified parameters and factors. These actions will contribute to optimizing the work performance of the staff and, therefore, to the overall success of the institution.